Prevención de lesiones no intencionales en niños de la Escuela José Ingenieros de Loja - Elizalde Oviedo, Wilman Favian (2019)
The World Health Organization (WHO) proposes to replace the word accident with unintentional injury in order to modify the conception that it is an inevitable fact and which can't be influenced. The accidents or unintentional injuries are a public health problem worldwide, however, although the risk can be reduced, a small percentage of these will always occur, which will require first aid. Therefore, the present research work “Prevention of unintentional injuries in children of the José Ingenieros School” was proposed, for which a descriptive, quantitative and cross-sectional study was conducted and a survey was applied to the teaching staff, whose results were analyzed using the IMB SPSS statistical program; obtaining that: the most frequent physical spaces causing unintentional injuries in children are the stairs in 42.9%, followed by the playground in 25.0%. In relation to the most frequent injuries that occur, 37.5% are open wounds, 32.1% closed wounds, produced in the anatomical regions are 46.4% lower limbs; upper limbs 32.1%; Regarding the activity in which more injuries occur are during recess with 26.8%, physical education with 21.4%. In addition, it was identified that 67.9% of teachers don't have knowledge related to first aid to intervene in that injuries. Therefore, the socialization of the results found with the authorities of the campus was carried out and a first aid manual was also delivered. KEY WORDS: Knowledge, Physical Spaces, Activity in children, Anatomical Region, First Aid.